Une statuette en bois et un dépôt rituel gallo-romains dans le puits IV du Crêt-Chatelard (Saint-Marcel-de-Félines, Loire) - Jean-Claude Béal; François Blondel (Revue Archéologique du Centre de la France)
An ancient wooden statuette of a “seated god” was discovered in a well in 1872 at Crêt-Chatelard (Saint-Marcel-de-Félines). Despite the age of this discovery, the artifact is still preserved today. This new study shows what furniture (basin, ceramics, fetters, basketry) was associated with it in the well. The date of realization of the statuette is specified by the 14C dating and specified by dendrochronology. The ensemble may have formed a ritual deposit of the second half of the 2nd century AD.